Intraocular Pressure and Optic Nerve Head Morphology during Scleral Lens Wear - Walker, Maria K. (Optom Vis Sci, 2020)
SIGNIFICANCE. Scleral lenses (SL) are increasing in scope and understanding their ocular health impact is imperative. The unique fit of a SL raises concern that the landing zone causes compression of conjunctival tissue that can lead to resistance of aqueous humor outflow and increased intraocular pressure (IOP). PURPOSE. To assess changes in optic nerve head morphology as an indirect assessment of IOP and evaluate other IOP assessment methods during SL wear. METHODS. Twenty-six healthy adults wore SL on one randomly selected eye for six hours while the fellow eye served as a control. Global minimum rim width (optical coherence tomography) and IOP (Icare, Diaton) were measured at baseline, two and six hours after SL application, and again post-SL removal. Central corneal thickness, anterior chamber depth, and fluid reservoir depth were monitored. RESULTS. Minimum rim width thinning was observed in test (−8 μm; 95% CI: −11 to −6 μm) and control (−6 μm; 95% CI: −9 to −3 μm) eyes after six hours of scleral lens wear (P < .01), although the magnitude of thinning was not significantly greater in the lens-wearing eyes (P = .09). Mean IOP (Icare) significantly increased +2 mm Hg (95% CI: +1 to +3 mm Hg) in the test eyes (P = .002), with no change in control eyes. Mean IOP change with Diaton was +0.3 mm Hg (95% CI: −0.9 to +3.2 mm Hg) in test eyes, and +0.4 mm Hg (95% CI: −0.8 to +1.7 mm Hg) in control eyes. However, Diaton tonometry showed poor within-subject variation and poor correlation with Icare. No clinically significant changes were observed in central corneal thickness or anterior chamber depth. CONCLUSIONS. This study suggests that SLs have a minimal effect on IOP homeostasis in the normal eye during SL wear, and an insignificant impact on the optic nerve head morphology in healthy adult eyes.